A Compendium of UNCTAD partnerships with civil society and the private sector (UN New YorkUS, 2016)
Summarises the different ways civil society, parliamentarians and private sector actors can engage in and contribute to UNCTAD's work. Provides information on the opportunities that exist for this purpose and gives examples of specific partnerships and cooperation with UNCTAD
Keywords: PARTNERSHIP